A new species of Dropephylla Mulsant & Rey, 1880 from northeastern Türkiye, and faunistic records of some species of Omaliini from Western Palaearctic Region (Coleoptera: Staphylinidae: Omaliinae) - Shavrin, Alexey V. (Zootaxa, 2024)
A new species of the genus Dropephylla Mulsant & Rey, 1880 is described and illustrated: D. loebli sp. nov. (northeastern Türkiye, Kars). Besides that, new faunistic data for 16 species (Omaliini) from the Western Palaearctic Region are provided. The aedeagus of D. cretica Jászay & Hlaváč, 2006 is illustrated. Several species are recorded from certain regions for the first time: D. caucasica (Kolenati, 1846) from Georgia, D. cretica from Türkiye and Lebanon, D. ioptera (Stephens, 1834) from Serbia, Phloeonomus (Phloeonomodes) minimus Erichson, 1839 from Ukraine, southwestern part of Russia and Türkiye, and Phyllodrepa floralis (Paykull, 1789) from Syria.